A Proposed Cost Accounting System and its Impact on Service Pricing in Vodafone Egypt (International Journal of Financial, Administrative and Economic Sciences, 2023)
This paper aims to propose a cost accounting system for a mobile company. Also, it aims to improve the quality of providing services to company clients. A questionnaire was used and distributed to collect data from clients. The collected data was manipulated and analyzed to obtain results. The study indicates that 74 respondents were obtained from these questionnaires. There were also interviews with employees of Vodafone Company and these were also analyzed. The results of the questionnaire were analyzed using the statistical software SPSS. The main findings revealed that the company is interested in the cost accounting system and service pricing significantly for development, in this case, the company is considering developing its basic system in terms of cost accounting and service pricing. It was also found in the results that the company is training employees in order to gain experience about the work they will work on. It is possible that employees will provide their ideas with the management in the event that they want to develop the system, so from the results it appears that the company is trying to progress significantly.
Keywords: Cost Accounting; Service Quality; Service Pricing; Vodafone